An interference suppression scheme with joint channel-data estimation. - Diggavi, S.N (IEEE Journal on selected areas in communications)
This paper describes an adaptive space-time receiver with joint channel-data estimation (JCDE) to combat time-varying (TV) multipath channels in the presence of undesired cochannel interference (CCI). The receiver uses a colored Gaussian metric for sequence detection in order to suppress the CCI. The proposed scheme also uses the knowledge of the transmit filter for improved channel estimation to enhance performance. The algorithm is derived as a quasi-Newton scheme on a chosen cost criterion and is also locally convergent. The performance of this class of interference cancellers is examined through the pairwise error probability (PEP). Through these expressions we gain insight into the properties of the canceller. The effect of channel dynamics and identification mismatch on the PEP is also examined. To reduce implementational complexity, a hybrid delayed-decision feedback and JCDE scheme is also proposed. The performance is illustrated using numerical results in realistic transmission environments